Penggunaan Hastag #samasamabelajar melalui Media TikTok terhadap Kebutuhan Informasi Generasi Z - Nursawiyah, Nursawiyah; Purwaningtyas, Franindya (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
In 2023, the social networking app Tik Tok is hugely popular. Sustainable development is within reach, and so is personal growth thanks to TikTok. Therefore, they can be very useful in spreading messages that encourage positive behavior change. TikTok campaigns on issues such as global warming, sexual violence, drug addiction, child labor, child and forced marriage, sexism in the workplace, and gender equality. Greater understanding and shifting perspectives can occur. The research intends to offer an analysis of how generation Z uses Tik Tok and #samasamabelajar hashtags to meet their information demands. A qualitative descriptive approach was taken to this investigation. Generation Z is the focus of this investigation into how hashtags on the Tik Tok app are used to fulfill requests for information. Information was collected from interviews with a sample of students at the Faculty of Social Sciences UIN Sumut. The findings reveal, first, that members of Generation Z have a strong preference for using the Tik Tok app. second, the typical content found on Tik Tok which is popular with generation Z. Finally, the information demands of generation Z are met through Tik Tok through #samasamabelajar hashtags. The writing of this article will provide new insights on how to leverage Tik Tok's social media platform for media through hashtags to meet the information needs of Generation Z and help them acquire and share new learning knowledge.